Penerapan Pembelajaran Terintegrasi dengan Penguatan Simulasi, Umpan Balik, dan Supervisi Akademik untuk Meningkatkan Kinerja Guru di SMK IB Khalifah Bangsa - s Iskandar (Jurnal Dewantara, 2019)
The subjects in this study were teachers of the Khalifah Bangsa Vocational School who were identified as having sufficient ability to apply variations in the learning methods of the 2018/2019 Academic Year. The study was conducted at IB Khalifah Bangsa Vocational School, located at Jl. Gelatik II, Purwoasri 28, Kecamatan Metro Utara, Kota Metro. Improving the ability of teachers to apply variations in learning methods that are in synergy with variations in class layout has encouraged more lively, directed, and quality learning in each teacher's classroom. Simulation, feedback, and academic supervision are the right tools to improve teacher skills and maintain them at all times. Teachers are able to streamline their time at school and make every activity effective for the sake of improving their abilities. Although not all methods, only between 8-15 methods mastered from 42 planned, one-way teaching habits that become cliched every implementation of learning can be minimized through the creation and application of integrative learning. Fostering supervisors as instructors is more authoritative and useful to be addressed immediately and at all times.